1990
DOI: 10.1029/jb095ib11p17605
|View full text |Cite
|
Sign up to set email alerts
|

A major 2.1 Ga event of mafic magmatism in west Africa: An Early stage of crustal accretion

Abstract: Birimian terranes from West Africa (Mauritania, Senegal, Ivory Coast, Burkina Faso, Niger) comprise two major units: a dominantly mafic bimodal volcanic unit and a volcano‐detrital unit with mostly felsic to intermediate protolith. Stratigraphic relationships of these units are still a matter of debate but current work suggest that they both formed in a short time interval around 2.1 Ga. Widespread basaltic magmas from the bimodal unit have been analyzed for REE distributions and Sr‐Nd isotopes. Three Sm‐Nd is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
263
0
8

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(317 citation statements)
references
References 110 publications
16
263
0
8
Order By: Relevance
“…These results and the geochemical data reveal the juvenile nature of these rocks reinforcing the interpretation that this region may be part of the Rhyacian juvenile continental magmatic arc, that extends through other parts of São Luís Craton with correspondence in the northeast portion of the Amazonian Craton and in West Africa (Abouchami et al 1990, Boher et al 1992, Wright et al 1995, Hirdes et al 1996.…”
Section: U-pb Geochronologymentioning
confidence: 59%
See 1 more Smart Citation
“…These results and the geochemical data reveal the juvenile nature of these rocks reinforcing the interpretation that this region may be part of the Rhyacian juvenile continental magmatic arc, that extends through other parts of São Luís Craton with correspondence in the northeast portion of the Amazonian Craton and in West Africa (Abouchami et al 1990, Boher et al 1992, Wright et al 1995, Hirdes et al 1996.…”
Section: U-pb Geochronologymentioning
confidence: 59%
“…On the African side, several studies based on structural, geochemical, geophysical and geochronological data demonstrate the existence of Archean and dominantly juvenile Paleoproterozoic crust (Abouchami et al 1990, Boher et al 1992, Gasquet et al 2003. On the Brazilian side, the northern part of the Amazonian Craton and São Luís Craton have demonstrated geochronological and evolutionary similarities.…”
Section: Introductionmentioning
confidence: 99%
“…From a consideration of the appearance of komatiites and komatiitic basalts that represent the products of plume-derived magmatism in Archean greenstone terranes, some authors have suggested that accretion of mantle plume-related oceanic plateaux at convergent plate margins may have played an important role in the growth of the continental crust throughout Earth's early history (e.g., Abouchami et al, 1990;Desrochers et al, 1993;Stein and Hofmann, 1994;Condie, 1997Condie, , 2005Puchtel et al, 1998;White et al, 1999). Nonetheless, it is well documented that the Archean continental crust is composed primarily of tonalite-trondhjemite-granodiorite (TTG) granitic rocks (up to 80%; Jahn et al, 1981;Rudnick, 1995;Condie, 2005).…”
Section: Implications For Continental Crustal Growthmentioning
confidence: 99%
“…Birimian volcanic gold belts generally extend for more than 100 km in length and up to 40 km in width and are separated by basins of isoclinally folded metasedimentary rocks averaging 90 km in width. The belts consist predominantly of metamorphosed tholeiitic to calc-alkaline basalts and form synclinoria that are made of variable proportions of metamorphosed basaltic lavas of bimodal composition comprising andesitic and dacitic pyroclastic rocks and rarely rhyolitic rocks (Abouchami et al, 1990).…”
Section: Geological Settingmentioning
confidence: 99%